(untitled) (Eastern Medical College Journal, 2024)
Background: Type 2 diabetes mellitus is a complex heterogeneous group of metabolic conditions characterized by increased levels of blood glucose due to impairment in insulin action and/or insulin secretion. The liver plays a major role in the regulation of carbohydrate metabolism, as it uses glucose as a fuel. Type 2 DM has been linked with dyslipidemia and elevation of some liver enzymes. Alanine Transaminase (ALT) is said to be a more specific enzymatic marker for liver injury. So, the objective of the present study is to assess the serum ALT level in type 2 diabetes mellitus and non-diabetic people and see its relationship with glycemic status. Materials and Methods: This was a hospital based cross-sectional comparative study comprising hundred (100) diagnosed type 2 diabetic patients and non-diabetic people aged between 31 and 70 years. This study was carried out in the department of Biochemistry, Eastern Medical College and department of Medicine, Eastern Medical College Hospital, Cumilla, Bangladesh from July 2022 to June 2023 with ethical clearance from respective IERB. Samples were taken by non-probability convenient sampling. Important variables in this study were FPG, HbA1c%, serum ALT and duration of diabetes. Results: Serum ALT level increased in 83% of type 2 diabetic cases and 24% in non-diabetic people. Serum ALT levels were significantly higher in type 2 diabetic patients than non-diabetic people (58.46±18.89 vs 33.93±15.02 U/L) and there were significant differences of serum ALT levels between good and poor control diabetes patients (42.40±11.05 vs 60.24±18.78 U/L. This study showed a positive correlation of serum ALT with FBS (p<0.00001), HbA1c% (p=0.02) and duration of diabetes (p=0.008) in the study cases. Conclusion: The results of the present study concluded that serum ALT levels were significantly increased in type 2 diabetic patients. Serum ALT is widely available and considered as a more specific marker for liver disease. Eastern Med Coll J. July 2024; 9 (2): 68-72